Pengembangan Media Pembelajaran Berbasis ICT dengan Metode Game-Based Learning Materi Statistika - Muhammad Fahreza Aditianata; Abdul Haris Rosyidi (MATHEdunesa, 2023)
This study describes the development of learning media based on ICT using game-based learning methods in statistical material and the results of its development are viewed from the criteria of the eligibility quality of the media. This research refers to the ADDIE Lee & Owens development model which consists of 5 stages, namely at the analysis stage, needs assessment and front-end analysis are carried out, the design stage is determining statistical material, navigation, flowcharts, and storyboards, the development stage is the process of making media and instrument validation ( validation sheet, pre-test, post-test and user response questionnaire) by two media experts and two material experts, the implementation stage was carried out by field trials on six class X students of a private high school in Sidoarjo, and the evaluation stage consisted of 3 levels, namely level 1 reactions, level 2 knowledge, and level 3 results. At this stage an assessment of the validation results was carried out from the media expert validator with 79.63% results in the appropriate category and material experts with 80.83% results in the appropriate category as an evaluation of level 2 knowledge, then an assessment of the results of the student respondent's questionnaire as an evaluation of level 1 reactions with a result of 80 .75% is in the proper category and the assessment level 3 results, obtained from the results of the pre-test and post-test. After that, the average rating of each aspect was added up from all validator assessments and student response questionnaires to determine the quality of the resulting media, which was 80.16%, according to quality criteria, categorized as feasible.